Chronology, petrology, geochemistry and tectonic environment of the Bailingshan complex in Eastern Tianshan, Xinjiang, NW China. (11th May 2018) - Fan, Shuanghu; Chen, Shu'e; Liu, Lei; Zhang, Yibin; Zhang, Li; Zhang, Tianyu; Yang, Liu‐Chen
Abstract : The Bailingshan complex distributed in the Jueluotage tectonic belt of Eastern Tianshan is composed of quartz monzodiorite, granodiorite, monzogranite, and granite. The petrography and petrochemistry of the complex have the features of metaluminous–high K calc‐alkaline series. The ages obtained by zircon U–Pb dating from different rocks indicate that quartz monzodiorite, granodiorite, monzogranite, and granite formed in 314.2 ± 3.5, 302.5 ± 3.8, 298.2 ± 3.6, and 310.9 ± 4.7 Ma, respectively, which is equivalent to the Late Carboniferous–Early Permian. The unconformity between the Lower Carboniferous and Upper Carboniferous in the Jueluotage tectonic belt indicates that the collisional orogen finished in the later period of the Early Carboniferous in this area, and that it began to enter the post‐collisional extension from the Late Carboniferous. The magmatic intrusion is a sign of the extensional activity of the Jueluotage tectonic belt in the Late Carboniferous–Early Permian.